Provider adherence to first antenatal care guidelines and risk of pregnancy complications in public sector facilities: a Ghanaian cohort study. Issue 1 (December 2016) - Amoakoh-Coleman, Mary; Klipstein-Grobusch, Kerstin; Agyepong, Irene; Kayode, Gbenga; Grobbee, Diederick; Ansah, Evelyn
Abstract Background Guideline utilization aims at improvement in quality of care and better health outcomes. The objective of the current study was to determine the effect of provider complete adherence to the first antenatal care guidelines on the risk of maternal and neonatal complications in a low resource setting. Methods Women delivering in 11 health facilities in the Greater Accra region of Ghana were recruited into a cohort study. Their first antenatal visit records were reviewed to assess providers' adherence to the guidelines, using a thirteen-point checklist. Information on their socio-demographic characteristics and previous pregnancy history was collected. Participants were followed up for 6 weeks post-partum to complete data collection on outcomes. The incidence of maternal and neonatal complications was estimated. The effects of complete adherence on risk of maternal and neonatal complications were estimated and expressed as relative risks (RRs) with their 95% confidence intervals (CI) adjusted for a potential clustering effect of health facilities. Results Overall, 926 women were followed up to 6 weeks post-partum. Mean age (SD) of participants was 28.2 (5.4) years. Complete adherence to guidelines pertained to the care of 48.5% of women. Incidence of preterm deliveries, low birth weight, stillbirths and neonatal mortality were 5.3, 6.1, 0.4 and 1.4% respectively. Complete adherence to the guidelines decreased risk of any neonatal complication [0.72 (0.65–0.93);p = 0.01 ] and delivery complication [0.66 (0.44–0.99), p  = 0.04]. Conclusion Complete provider adherence to antenatal care guidelines at first antenatal visit influences delivery and neonatal outcomes. While there is the need to explore and understand explanatory mechanisms for these observations, programs that promote complete adherence to guidelines will improve the pregnancy outcomes.